JEJAK KEMERDEKAAN: INOVASI WEBSITE PEMBELAJARAN SEJARAH PADA MATERI PERJUANGAN MEMPERTAHANKAN KEMERDEKAAN - Ulul Azmi Mustari; Evi Alfira; Rizal Arizaldy Ramly Ramly (Jurnal Kependidikan Media, 2026)
Grade XII students have diverse characteristics and learning abilities in understanding historical material, especially in the material of the struggle to defend Indonesian independence. The problem faced in learning history is the use of conventional learning methods so that students are less interested and have difficulty understanding history material. This research aims to develop a history learning website for the Trail of Independence and to determine the level of validity, practicality, and effectiveness of the website in learning history in grade XII. This research uses the Research and Development (R&D) method with a 4-D development model consisting of four stages, namely define, design, develop, and disseminate. The website developed is then tested for feasibility through validation of material experts and media experts, teacher and student response tests, and effectiveness tests using pretests and posttests. The results of the study show that the level of website validity obtained a very valid category with an average material validation of 3.85 and media validation of 3.75. The level of practicality based on the students' responses obtained an average of 3.50 with the very practical category, while the teacher's response obtained an average of 3.79 with the very practical category. The level of website effectiveness can be seen from the increase in student learning outcomes, with an average pretest score of 58.20 and posttest of 90.00. Thus, the Independence Trail history learning website is declared feasible to be used as a digital technology-based history learning medium that is able to increase students' motivation and learning outcomes.   Keywords: Website; History Learning; Traces of Independence.     Referensi Alghiffari, E. K., Alam, R., & Siswanto, D. H. (2024). Tren Publikasi Terkait Model Pengembangan 4D pada Pendidikan. JPT, 3(5), 1–0. Alim, M. R. (2025). Pengembangan Gallery Visual Sejarah (GVS) Pada Materi Sejarah Lokal Brigade Ronggolawe Berbasis Web. Sajaratun, 10(1), 21–26. Ariandini, N., & Ramly, R. A. (2023). Penggunaan multimedia pembelajaran interaktif dalam meningkatkan hasil belajar siswa. Jurnal Kependidikan Media, 12(2), 107-116. Arizaldy, R., & Alfadil, M. T. (2021). The influence of the application of power point learning media on ict learning outcomes. Jurnal Galeri Pendidikan, 1(01), 479. Ayu, S. Virtual Reality (VR) to Revitalize History in Learning. Ayu, S., & Ramly, R. A. (2024). Pengaruh Model Mixed Reality Terhadap Kemampuan Berpikir Kronologis Siswa. PROSIDING UNIVERSITAS KRISTEN INDONESIA TORAJA, 4(1), 30-36. AYU, S., SYATRIANA, E., AKIB, E., NURLINA, N., LATIF, F., & RAMLY, R. (2024). Implementation of Technologocal Pedagogical Content Knowledge (TPACK) in the Malaysian-Indonesian National School. INTERNATIONAL JOURNAL, 11(10), 282. Darmawati, A., Marwan, M., Suhenrik, P., Ramly, R. A., & Salam, S. (2023). Adaptive Learning in the Independent Curriculum: Integration of Behavioristic, Cognitive and Constructivist Theories in Educational Technology. International Journal of Education, Vocational and Social Science, 2(04), 255-265. Darnawati, Jamiludin, & Lenisa. (2022). Peningkatan Hasil Belajar Sejarah Siswa dengan Memanfaatkan Media Cerita Bergambar. Sebatik, 26(2), 739–745. https://doi.org/10.46984/sebatik.v26i2.2049 Dewi, N. P., Adi, E. P., & Oktaviani, H. I. (2025). Pengembangan Multimedia Interaktif Berbasis Website Dengan Objek 3D Viewer Pada Materi Kehidupan Masyarakat Masa Pra Aksara di Indonesia Mata Pelajaran Sejarah Kelas X SMA. Journal of Educational Technology Studies and Applied Research, 2, 1–12. https://doi.org/10.70125/jetsar.v2i1y2025a44 Firmansyah, H. (2024). Implementasi Model Pembelajaran Kooperatif untuk Meningkatkan Keterampilan Berpikir Kritis pada Siswa dalam Pembelajaran Sejarah. JIMPS, 9(2), 524–532. https://doi.org/10.24815/jimps.v9i2.30440 Fitriyani, & Teguh Nugroho, A. (2022). Literasi Digital Di Era Pembelajaran Abad 21. Literasi: Jurnal Pengabdian Masyarakat Dan Inovasi, 2(1), 307–314. https://doi.org/10.58466/literasi.v2i1.1416 Hastuti, D. N. A. E., Widyanti, R. H. D., Salam, S., Prayogi, A., Alfira, E., & Ramly, R. A. ILMU SEJARAH. Judijanto, L., Muhammadiah, M., Utami, R. N., Suhirman, L., Laka, L., Boari, Y., … Yunus, M. (2024). Metodologi Research and Development. Jambi: Sonpedia Publishing Indonesia. Retrieved from www.buku.sonpedia.com Khasanah, U., & Hartati, U. (2022). Pengembangan Komik Sejarah Pada Materi Agresi Militer Belanda Ke 2 di Metro. Swarna Dwipa, 6(2), 2022. Kurniati, R., & Ramly, R. A. (2022). Development of macromedia flash module in the learning media course faculty of teacher training and education university of pejuang republik Indonesia. MaPan: Jurnal Matematika Dan Pembelajaran, 10(2), 366-384. Lantang, F. A. A., & Ramly, R. A. (2025). Implementation of Goesmart Social Networking Site as a Learning Media In Ict Subjects For Students Class VII. INDONESIAN JOURNAL OF EDUCATIONAL TECHNOLOGY, 4(1), 21-28. Lukman. (2025). Metode Penelitian Pengembangan Pendidikan. Riau: Bravo Press. Mustari, U. A., & Alfira, E. (2026). Eksplorasi Pengalaman Belajar Siswa melalui Game Kuis Digital Quizizz dalam Pembelajaran Sejarah. Magau Historia Jurnal, 1(1), 15–27. Mustari, U. A., Alfira, E., Ramly, R. A., P, S., Salam, S., Marwan, & Ariaty, E. B. (2025). Pengembangan Modul Kearifan Lokal sebagai Upaya Pelestarian Rumah Tongkonan melalui Pendidikan. Equilibrium, 13(3), 464–480. Retrieved from https://journal.unismuh.ac.id/index.php/equilibrium/index Mustika, T. P., Sari, F. A., Susilo, E., Zulhafizh, Rachman, N. Y., & Ramadhan, I. (2025). Workshop Pengembangan Media Pembelajaran Berbasis Website untuk Meningkatkan Kompetensi Guru dalam Pembelajaran Mendalam. SOLMA, 14(3), 4328–4340. https://doi.org/10.22236/solma.v14i3.20917 Noer, R. Z., Mustopa, D., Ramly, R. A., Nursalim, M., & Arianto, F. (2023). Landasan Fılosofıs Dan Analısıs Teorı Belajar Dalam Implementası Kurıkulum Merdeka Dı Sekolah Dasar. Jurnal Elementaria Edukasia, 6(4), 1559-1569. Okpatrioka. (2023). Research And Development (R&D) Penelitian Yang Inovatif Dalam Pendidikan. Dharma Acariya Nusantara, 1(1), 86–100. Pratama, I. G., Hanif, M., Ramly, R. A., & Khotimah, D. K. (2023, July). Pengembangan media belajar pjok berbasis aplikasi smart learning di masa pandemi. In SIPTEK: Seminar Nasional Inovasi Dan Pengembangan Teknologi Pendidikan (Vol. 1, No. 1). Pratama, I. G., Mustaji, M., Mariono, A., & Ramly, R. A. (2026). Analyzing VR-SL Models in Physical Education: a study of Indonesian educational institutions based on the e-readiness model. Retos, 77, 220-237. Purmintasari, Y. D., & Lesmana, C. (2023). Pengembangan Media Pembelajaran Interaktif Edpuzzle dalam Pembelajaran Sejarah. Fajar Historia: Jurnal Ilmu Sejarah Dan Pendidikan, 7(2), 197–209. https://doi.org/10.29408/fhs.v7i2.12370 Putri, A. E. (2024). Penggunaan Media Pembelajaran Berbasis Digital dalam Pembelajaran Sejarah untuk Meningkatkan Minat Belajar Peserta Didik. JIMPS, 9(2), 533–540. https://doi.org/10.24815/jimps.v9i2.30523 Ramly, R. A. (2021). Penerapan komunitas belajar melalui aplikasi whatsapp sebagai upaya meningkatkan aktivitas belajar sejarah. Biormatika: Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 7(2), 147-Ã. Ramly, R. A. (2022). Peran Komunikasi Orang Tua Terhadap Pembentukan Karakter Anak Yang Berakhlakul Karimah. Connected: Jurnal Ilmu Komunikasi, 25-37. Ramly, R. A., & Ayu, S. (2022). Pengaruh Media Sosial Terhadap Hasil Belajar Siswa. Jurnal Kependidikan Media, 11(3), 107-119. Ramly, R. A., & Ayu, S. (2025). Pemanfaatan ChatGPT dan AI Sebagai Asisten Pembelajaran: Pelatihan dan Pengembangan Media Pembelajaran. Tongkonan: Jurnal Pengabdian Masyarakat, 4(2), 193-204. Ramly, R. A., & Ilham, I. (2022). Penggunaan Quipper School Terhadap Hasil Belajar Siswa Smp Negeri 2 Campalagian Polewali Mandar. Jurnal Kependidikan Media, 11(2), 65-74. Ramly, R. A., & Latiff, Z. A. (2021). Secondary Teachers Perception on the Effectiveness of Google Classroom As a Learning Medium During Movement Control Order (MCO). Journal of Media and Information Warfare, 14(1), 1-10. Ramly, R. A., Ariaty, E., & Ariandini, N. (2025). IMPLEMENTASI MODEL FLIPPED CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR. Jurnal Kependidikan Media, 14(1), 1-13. Ramly, R. A., Riyanto, Y., Susarno, L. H., B, E. A., A, D., & Ayu, S. (2026). Virtual Reality (VR) to Revitalize History in Learning. Wyyw, 10(1), 1551–1563. Ramly¹, R. A., & Alfadil, M. T. Jurnal Galeri Pendidikan. Saidah, N., Jati, S. S. P., & Ridhoi, R. (2023). Pengembangan Website Gasing: Galaxy of Singhasari untuk pembelajaran sejarah kelas X IPA-E SMAN I Singosari. Historiography, 3(2), 275–285. Salam, S., Ramly, R. A., Marwan, M., & Irwan, I. (2026). Development and Validation of an Augmented Reality-Based Learning Module to Enhance Historical Understanding in Secondary Education. QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 18(1), 601-616. Salam, S., Suhenrik, P., Ramly, R. A., & Ampa, A. T. (2026). PENGUATAN KESADARAN BUDAYA SISWA MELALUI WORKSHOP BUDAYA LOKAL BERBASIS EDUKASI PARTISIPATIF. PEDAMAS (PENGABDIAN KEPADA MASYARAKAT), 4(02), 604-614. Suharni. (2021). Upaya Guru dalam Meningkatkan Motivasi Belajar Siswa. G-Couns: Jurnal Bimbingan Dan Konseling, 6(1), 172–184. Suhenda, D., Fuad, F., Sekti, P. H., Syaefudin, D., & Sukmawati, N. (2024). Pengembangan Media Pembelajaran Interaktif dalam Konteks Pendidikan Modern. Educatus, 2(3), 16–23. https://doi.org/10.69914/educatus.v2i3.22 Suhendrik, P., Ramly, R. A., Salam, S., Marwan, M., & Irwan, I. (2026). Development of Local Wisdom-Based E-Modules for Strengthening Education and Cultural Tourism in Tanah Toraja Regency. QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 18(1), 617-632. Suhenrik, P., Salam, S., Ramly, R. A., Marwan, M., Alfira, E., & Mustari, U. A. (2025). Teacher Capacity Building in Developing Project-Based Learning Model in Toraja. Jurnal Perjuangan dan Pengabdian Masyarakat: JPPM, 1(3), 30-37. Susilo, A., & Sofiarini, A. (2020). Peran Guru Sejarah dalam Pemanfaatan Inovasi Media Pembelajaran. Jurnal Komunikasi Pendidikan, 4(2), 79–93. Retrieved from http://journal.univetbantara.ac.id/index.php/komdik Suyanti, P., Fatimah, P. S., & Rudianto, A. (2025). Pengembangan Media Pembelajaran Quizizz berbasis Gamifikasi menggunakan Model 4D pada Materi Hak dan Kewajiban Kelas IV Madrasah Ibtidaiyah. EL-Muhbib: Jurnal Pemikiran Dan Penelitian Pendidikan Dasar, 9(2), 433–447. https://doi.org/10.52266/el-muhbib.v9i2.4916 Zamsiswaya, Sawaluddin, & Sihombing, B. (2024). Model Pengembangan 4D (Define, Design, Develop, dan Disseminate) dalam Pembelajaran Pendidikan Islam. Journal of Islamic Education El Madani, 4(1), 11–19.